The Development of Interactive Learning Media for Occupational Safety and Health (OSH) Based on Project-Based Learning to Enhance Students Decision Making Skills - Rubbayyi Shaffiyyah; Khoirun Nikmatul Laili; Adibah Bahrak; Ayu May Vitasari; Nila Rahmawati (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to develop and design interactive learning media based on Project-Based Learning (PjBL) in the field of Occupational Safety and Health (OSH) to enhance students’ decision-making skills. The development of this media is specifically intended to train decision-making abilities, as in the context of OSH, students are required not only to possess adequate knowledge but also to make appropriate decisions in high-risk situations. This study employed a Research and Development (R&D) approach using the 4D development model, which consists of the define, design, development, and disseminate stages. The product developed is a web-based interactive learning media using the Genially platform, incorporating simulation scenarios of construction project conditions. The learning media is integrated with the Project-Based Learning model, which is expected to improve student engagement, critical thinking skills, and decision-making abilities. Keywords: Interactive media, Project-based learning, decision making, occupational safety and health